Development of Wireless and Passive SAW Temperature Sensor with Very High Accuracy - Gao, Xu; Cheng, Lina; Xue, Xufeng; Zhai, Shoupei; Liang, Yong; Wang, Wen; Liu, Mengwei; Zhu, Jialiang; Li, Zhuoyue (Applied sciences, 2021)
A surface acoustic wave (SAW) temperature sensor with high accuracy was developed and wirelessly characterized in this work. The sensing chip with reflective delay line pattern was simulated using typical coupling of modes (COM) model and prepared by the standard photolithographic technique. Sharp reflection peaks with high signal-to-noise (SNR) were observed from the developed sensing chip operating at 433 MHz. Referring to the frequency-stepped continuous wave (FSCW)-based transceiver, planar antennas, and the developed SAW chip, the wireless and passive temperature sensor system was built. Adaptive Least Mean Square (LMS) algorithm was used for the first time in the SAW sensor signal processing to significantly improve the system SNR, and the corresponding phase fluctuation is down to only 3°. High temperature sensitivity of 36.5 °C and very high accuracy of ±0.2 °C in the range of −30 °C∼100 °C were achieved successfully by wireless measurement.